Adaptation and Convergent Evolution within the Jamesonia-Eriosorus Complex in High-Elevation Biodiverse Andean Hotspots - Sánchez-Baracaldo, Patricia (Public Library of Science, 2014)
The recent uplift of the tropical Andes (since the late Pliocene or early Pleistocene) provided extensive ecological opportunity for evolutionary radiations. We test for phylogenetic and morphological evidence of adaptive radiation and convergent evolution to novel habitats (exposed, high-altitude páramo habitats) in the Andean fern genera Jamesonia and Eriosorus. We construct time-calibrated phylogenies for the Jamesonia-Eriosorus clade. We then use recent phylogenetic comparative methods to test for evolutionary transitions among habitats, associations between habitat and leaf morphology, and ecologically driven variation in the rate of morphological evolution. Páramo species (Jamesonia) display morphological adaptations consistent with convergent evolution in response to the demands of a highly exposed environment but these adaptations are associated with microhabitat use rather than the páramo per se. Species that are associated with exposed microhabitats (including Jamesonia and Eriorsorus) are characterized by many but short pinnae per frond whereas species occupying sheltered microhabitats (primarily Eriosorus) have few but long pinnae per frond. Pinnae length declines more rapidly with altitude in sheltered species. Rates of speciation are significantly higher among páramo than non-páramo lineages supporting the hypothesis of adaptation and divergence in the unique Páramo biodiversity hotspot.